2000
DOI: 10.1095/biolreprod62.3.755
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Distribution of NHE1 and NHE2 in the Rat Epididymis

Abstract: Previous studies from our laboratory have provided evidence that the rat epididymis utilizes the Na(+)/H(+) exchanger to transport acid and base. The present study was undertaken to use immunohistochemistry for investigating the localization (apical versus basolateral) and distribution of NHE1 and NHE2 proteins along intact rat epididymis. Both proteins were found to be exclusively localized within the epithelium. Immunoreactivity for NHE1 was detected on the basolateral surface, whereas NHE2 immunoreactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…These proteins serve important functions in regulating intracellular pH, cell volume, acid-base balance, and neutral NaCl absorption (43,44). NHE8 joins NHE1, NHE2, NHE3, and NHE10 as NHE isoforms detected in the testis (6,14,38). Previously, we detected NHE8 mRNA in human testis (unpublished observation), and others detected NHE8 mRNA in mouse testis (12).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…These proteins serve important functions in regulating intracellular pH, cell volume, acid-base balance, and neutral NaCl absorption (43,44). NHE8 joins NHE1, NHE2, NHE3, and NHE10 as NHE isoforms detected in the testis (6,14,38). Previously, we detected NHE8 mRNA in human testis (unpublished observation), and others detected NHE8 mRNA in mouse testis (12).…”
Section: Discussionmentioning
confidence: 78%
“…NHE1, a ubiquitously expressed isoform, is detected in virtually all cell types in the testis. NHE2 and NHE3 are expressed on the apical membrane of epithelial cells in the efferent and epididymal ducts (6,14,29,46). NHE8 mRNA was detected in mouse testis (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Na + transportation is actively linked to H + secretion and fluid reabsorption (Wong and Yeung et al, 1978;Chew et al, 2000). Immunofluorescence showed that the Na + -K + -ATPase 1 subunit, NHE3 and Aqp9 were markedly reduced in the efferent ducts and caput epididymis in adult Gpr48 -/-mice ( Fig.…”
Section: Reduced Expression Of Water and Ion Transporters In Reproducmentioning
confidence: 94%
“…Different sets of transporters, expressed in specific cell types in different segments of the epididymal tubule, participate in the progressive decrease in bicarbonate concentration and pH that occurs as the fluid flows through the lumen of the epididymis (reviewed by Da Silva et al, 2007b;Pastor-Soler et al, 2005). Significant bicarbonate reabsorption occurs in the initial segments and caput of the epididymis (Levine and Kelly, 1978;Levine and Marsh, 1971) via the sodium-hydrogen exchangers NHE2 and NHE3 (Bagnis et al, 2001;Cheng Chew et al, 2000) located in the apical membrane of principal cells, and the basolateral anion exchanger AE2 (Jensen et al, 1999b) and sodium-bicarbonate cotransporter NBC-e1 (also known as SLC4A4) (Jensen et al, 1999a). Clear cells, which express high levels of the vacuolar proton pumping ATPase, V-ATPase, are involved in luminal acidification in the distal epididymis (Breton et al, 1996;Brown et al, 1992;Herak-Kramberger et al, 2001;Pietrement et al, 2006).…”
Section: Introductionmentioning
confidence: 99%